2017
DOI: 10.1001/jamainternmed.2017.3877
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oral vs Transdermal Estrogen Therapy on Sexual Function in Early Postmenopause

Abstract: IMPORTANCE Sexual dysfunction, an important determinant of women's health and quality of life, is commonly associated with declining estrogen levels around the menopausal transition.OBJECTIVE To determine the effects of oral or transdermal estrogen therapy vs placebo on sexual function in postmenopausal women. DESIGN, SETTING, AND PARTICIPANTSAncillary study of the Kronos Early Estrogen Prevention Study (KEEPS), a 4-year prospective, randomized, double-blinded, placebo-controlled trial of menopausal hormone th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 46 publications
0
50
0
1
Order By: Relevance
“…However current updated guidelines from the International Society for Sexual Medicine state that data do not support the use of systemic estrogen for any postmenopausal sexual dysfunction adding that vaginal estrogen's benefit to dryness and dyspareunia may increase sexual motivation (Santoro et al, 2016). A later study suggests that transdermal rather than oral route may benefit low sexual desire (Taylor et al, 2017) but only on a temporary basis.…”
Section: Clinical Implications Of Findingsmentioning
confidence: 99%
“…However current updated guidelines from the International Society for Sexual Medicine state that data do not support the use of systemic estrogen for any postmenopausal sexual dysfunction adding that vaginal estrogen's benefit to dryness and dyspareunia may increase sexual motivation (Santoro et al, 2016). A later study suggests that transdermal rather than oral route may benefit low sexual desire (Taylor et al, 2017) but only on a temporary basis.…”
Section: Clinical Implications Of Findingsmentioning
confidence: 99%
“…[ 24 ] In a randomized clinical trial of 670 women with reduced sexual function, sexual function was improved by transdermal E2 (t‐E2) therapy compared with a placebo, with the t‐E2 treatment associated with a significant increase in average vaginal lubrication and decreased pain. [ 25 ] In men, endocrine erectile dysfunction can be common, and T plays a crucial role in regulating the expression of NO synthase and phosphodiesterase type‐5 inhibitor in the penis. [ 26 ] T replacement therapy is therefore often used, and one investigation showed that improvements in erectile dysfunction were significantly enhanced in male patients with hypogonadism who received T therapy, compared to a placebo (57% versus 16.7%).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study suggest that HT in menopausal women may reduce frailty. Although specific measures of frailty were not measured in KEEPS and the women were relatively young (mean age 55 years), some chronic conditions of aging, [decreases in bone mineral density, sleep disturbances, depression, vaginal atrophy, and deposition of β amyloid in the brain], were alleviated by the HT treatments (Cintron et al, 2017;Farr, Khosla, Miyabara, Miller, & Kearns, 2013;Gleason et al, 2015;Kantarci et al, 2016;Taylor et al, 2017). In older women of Estrogen Early versus Late Intervention with Estadiol (ELITE), estrogen treatments reduced the rate of increase of carotid intima-medial thickness (Hodis et al, 2016), a result consistent with the finding of this study that estrogen lowered the endothelial-prominent GDF15 SASP.…”
Section: Discussionmentioning
confidence: 99%